Islamic history a very short introduction - Silverstein, Adam J. (Oxford ; New York : Oxford University Press, 2010)
Does history matter? This book argues not that history matters, but that Islamic history does. This Very Short Introduction introduces the story of Islamic history; the controversies surrounding its study; and the significance that it holds - for Muslims and for non-Muslims alike.Opening with a lucid overview of the rise and spread of Islam, from the seventh to twenty first century, the book charts the evolution of what was originally a small, localised community of believers into an international religion with over a billion adherents.
Includes bibliographical references (p. 141-145) and index.
Description based on print version record.
Keywords: Islam -- History; Electronic books; Electronic books